On The Features of the Negative Temperature Coefficient Phenomenon in Combustion of N-Pentane-Air Mixtures - Rubtsov, N.M; Borisov, A.A; Skachkov, G. I; Troshin, K. Ya (International Journal of Chemical and Process Engineering Research, 2014)
The ignition of n-pentane-air mixture at low temperatures is experimentally studied in a rapid mixture injection static reactor. The ignition process was monitored using a high speed color video camera. It is shown that introduction of platinum wire into the reactor eliminates the phenomenon of negative temperature coefficient; however Pt wire has no effect on the ignition delay time of thermal ignition of stoichiometric n-pentane-air mixture at lower temperatures.